Kurt Grote at 185 m of His Winning 200 m Breaststroke Race at the 1998 Goodwill Games in New York - Rushall, B. S. (1999)
Video pictures (17 frames) and the appropriate technical/ biomechanical explanations for Kurt Grote at 185 m of His Winning 200 m Breaststroke Race at the 1998 Goodwill Games in New York.